Emerging role of selective autophagy in human diseases - Mizumura, Kenji; Choi, Augustine M. K.; Ryter, Stefan W. (Frontiers in Pharmacology, 2014)
Abstract Autophagy was originally described as a highly conserved system for the degradation of cytosol through a lysosome-dependent pathway. In response to starvation, autophagy degrades organelles and proteins to provide metabolites and energy for its pro-survival effects. Autophagy is recognized as playing a role in the pathogenesis of disease either directly or indirectly, through the regulation of vital processes such as programmed cell death, inflammation, and adaptive immune mechanisms. Recent studies have demonstrated that autophagy is not only a simple metabolite recycling system, but also has the ability to degrade specific cellular targets, such as mitochondria, cilia, and invading bacteria. In addition, selective autophagy has also been implicated in vesicle trafficking pathways, with potential roles in secretion and other intracellular transport processes. Selective autophagy has drawn the attention of researchers because of its potential importance in clinical diseases. Therapeutic strategies to target selective autophagy rather than general autophagy may maximize clinical benefit by enhancing selectivity. In this review, we outline the principle components of selective autophagy processes and their emerging importance in human disease, with an emphasis on pulmonary diseases.